Stormy : a story about finding a forever home - Guojing, 1983- (New York : Schwartz & Wade Books, 2019)
In this wordless picture book, a lonely stray dog is befriended by a kind woman.
Keywords: Dogs -- Juvenile fiction; Animal rescue -- Juvenile fiction; Dogs -- Fiction; Animal rescue -- Fiction; Stories without words